2017
DOI: 10.3389/fimmu.2017.00543
|View full text |Cite
|
Sign up to set email alerts
|

Major CD4 T-Cell Depletion and Immune Senescence in a Patient with Chronic Granulomatous Disease

Abstract: Chronic granulomatous disease (CGD) results from primary defects in phagocytic reactive oxygen species (ROS) production. T-cell evaluation is usually neglected during patients’ follow-up, although T-cell depletion has been reported in CGD through unknown mechanisms. We describe here a 36-year-old patient with X-linked CGD with severe CD4 T-cell depletion <200 CD4 T-cells/μl, providing insights into the mechanisms that underlie T-cell loss in the context of oxidative burst defects. In addition to the typical in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3
3

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 42 publications
1
3
0
Order By: Relevance
“…We noticed unexpectedly that one of the five patients with chronic granulomatous disease (CGD), a phagocyte defect, had a low TREC count, an observation that was previously observed in some patients with CGD, which is thought to be due to T cell depletion (through unknown mechanisms) [43,44]. This finding supports our observation, and calls for additional comprehensive T cell evaluation and monitoring in these patients.…”
Section: Discussionsupporting
confidence: 87%
“…We noticed unexpectedly that one of the five patients with chronic granulomatous disease (CGD), a phagocyte defect, had a low TREC count, an observation that was previously observed in some patients with CGD, which is thought to be due to T cell depletion (through unknown mechanisms) [43,44]. This finding supports our observation, and calls for additional comprehensive T cell evaluation and monitoring in these patients.…”
Section: Discussionsupporting
confidence: 87%
“…1). Previous studies reported contradictory observations, where increased, reduced or not affected T cell numbers were shown (83)(84)(85)(86). The discrepancy between findings might be due to the differential treatment of patients at the time of analysis, different distribution of patients' age or causative mutations in p91 phox or p47 phox coding genes within cohorts.…”
Section: Discussionmentioning
confidence: 95%
“…Reduced naive T cell pools are a characteristic feature of aging and may contribute to the impaired immune responses observed in elderly individuals 38 . Depletions in naive T cell populations, and the corresponding de cits in adaptive immune responses, have also been reported in in ammatory states like chronic hepatitis C infection 39 and chronic granulomatous disease 40 ; however, this phenomenon has been less well documented in solid organ transplantation. Additionally, it has been consistently observed that solid organ transplant recipients develop poor adaptive response to new antigens either during immunization or new infections -including SARS-CoV-2 mRNA vaccination [41][42][43] .…”
Section: Discussionmentioning
confidence: 99%